Geotechnical Evaluation of Soil in Taza District, Southeast of Kirkuk, Iraq: Correlation Between Chemical and Some Physical Properties (Iraqi National Journal of Earth Science (INJES), 2026)
Soil is one of the most important natural resources. A comprehensive geotechnical soil assessment must be performed when starting any engineering project to avoid future damage. The properties of soil and concrete are greatly affected by the chemical composition, which makes understanding statistical relationships between soil properties essential in the study, planning, and preliminary design stages of engineering projects, saving time and money. This research aims to evaluate some geotechnical properties of the soil in Taza district, SE of Kirkuk for ten locations distributed across the district and use mathematical relationships to predict the physical properties (fines ratio, LL, PL, PI) based on the chemical properties of the soil (pH, TDS, OM, SO3, Cl⁻, gypsum) Using simple and multiple linear regression analysis. The results of particle size analysis show that coarse soils predominate in sites T1, T2, and T10(1), while fine soils, especially silt, in sites T3–T10, with an average of 50.53% for all sites. The soil can be classified into low-plastic clay (CL) and low-plastic silt (ML) according to the plasticity chart, with medium liquidity and plasticity index values ranging from low to medium. The results of the standard compaction test show similar values for the optimum moisture content and maximum dry density. Specific gravity values range between 2.64 and 2.81, and chemical tests show that site T10 recorded clear increases in most properties. The results of Simple Linear Regression Analysis (SLRA) show an inverse relationship between the chlorine percentage and some physical properties, while Multiple Linear Regression Analysis (MLRA) shows stronger relationships between the variables.
Keywords: Taza, Soil, Plasticity, Correlation, Regression